Promoting eco-agritourism using an augmented reality-based educational resource: a case study of aquaponics. Issue 7 (18th August 2022) - Garzón, Juan; Acevedo, Juan; Pavón, Juan; Baldiris, Silvia
ABSTRACT: Agritourism is a type of ecological tourism that combines agricultural activities with tourism. There is a growing interest in this industry worldwide, which poses both opportunities and challenges for social and natural environments. Grounded on the theory of situated learning, we developed an augmented reality-based educational resource to promote eco-agritourism – namely, to promote agritourism while encouraging tourists to be environmentally responsible. This study presents the results of an educational experiment that compared the scores of students who were instructed using a combination of the augmented reality-based educational resource and the professor's guidance with those of students who were instructed only by the professor. The study analyzed the learning outcomes and the degree of users' motivation to learn about aquaponics in an agritourism farm. The participants were 40 volunteers who had no previous knowledge about aquaponics. The results show that the resource has a medium effect size on learning gains and a large effect on knowledge retention. Likewise, the data indicates that the resource increased users' motivation to learn and practice responsible agritourism. These results seem to indicate that augmented reality-based resources are appropriate for promoting eco-agritourism and encourage tourists to develop a positive bond with nature.